Delta-Sigma A/D Converters in the Applications of Metrological Versus Acoustic Systems - Tadeusz Sidor (New Approaches in Engineering Research Vol. 7, 2021)
Delta-Sigma A/D converters are now widely used to record sounds and music in digital acoustic systems. In measurement systems, such converters can be used to convert analogue voltage signals to digital signals. The quality requirements of converters used in measurement systems (accuracy) and acoustic systems (S/N ratio) are, however, clearly different. The purpose of this paper is to highlight the differences in requirements for both types of applications.